(untitled) (Submission and Review of Research -Biological Sciences Series, 2025)
The genetic diversity of two species of Syrian bats, the fruit-eating Rousettus aegyptiacus and the insectivorous Pipistrellus kuhlii, was studied and the degree of genetic kinship between them was determined; using the Inter Simple Sequence Repeats (ISSR) technique. The research was carried out in the biotechnology laboratories of the General Authority for Atomic Energy in Damascus during the year 2023/2024. We isolated DNA from the muscle tissue of two species of bats and verified its quality and quantity, then performed the polymerase chain reaction. For this purpose, 15 primers were used, 11 of which gave amplification products in the PCR reaction. These 11 primers proved effective in distinguishing between the two studied species and giving polymorphism. The use of these primers resulted in a total of (41) with an average of (3.72) bands. The total number of bands for each primer ranged between (1) band as the lowest number with primer (Oligo 9) and (9) bands as the highest number with primer (Oligo 12) with an average of (3.72) bands. The number of morphologically multiple bands was (21) with an average of (1.9) bands. The number of morphologically diverse bands for each primer ranged between (1) band as the lowest number with primer (Oligo 1, Oligo 5, Oligo 8, Oligo 9, Oligo 12, Oligo 13) and (4) bands as the highest number with primer (Oligo 6). The cluster analysis and degree of kinship showed the presence of genetic divergence between the two species at a distance of 0.67, meaning that the percentage of genetic divergence between the two studied species was 67%.